2022
DOI: 10.1111/odi.14286
|View full text |Cite
|
Sign up to set email alerts
|

PINK1‐mediated mitophagy reduced inflammatory responses to Porphyromonas gingivalis in macrophages

Abstract: ObjectiveMitochondria are strained by microbial stimuli in the periodontal niche. Damaged mitochondria are cleared by mitophagy. The purpose of the study was to explore whether mitophagy participated in the progress of periodontitis and whether activation of mitophagy can inhibit inflammatory responses to bacterial infection in macrophages.MethodsMitophagy‐related genes were measured in the healthy and inflamed human gingiva. Bone marrow‐derived macrophages (BMDMs) were infected with Porphyromonas gingivalis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…In addition, P. gingivalis infection has been shown to impair the expression of the canonical PD-related proteins PTEN-induced putative protein kinase 1 (PINK1) and Parkin, two proteins critically involved in clearing damaged or dysfunctional mitochondria by mitophagy. 44 Mutations in PINK1 and PARK2 (the gene for Parkin) are involved in PD pathogenesis. 45 In P. gingivalisinfected bone marrow-derived macrophages, infection resulted in decreased mRNA transcription and protein expression of both PINK1 and Parkin, leading to an inhibition of mitophagy and a resultant accumulation of damaged mitochondria and reactive oxygen species (ROS).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, P. gingivalis infection has been shown to impair the expression of the canonical PD-related proteins PTEN-induced putative protein kinase 1 (PINK1) and Parkin, two proteins critically involved in clearing damaged or dysfunctional mitochondria by mitophagy. 44 Mutations in PINK1 and PARK2 (the gene for Parkin) are involved in PD pathogenesis. 45 In P. gingivalisinfected bone marrow-derived macrophages, infection resulted in decreased mRNA transcription and protein expression of both PINK1 and Parkin, leading to an inhibition of mitophagy and a resultant accumulation of damaged mitochondria and reactive oxygen species (ROS).…”
Section: Discussionmentioning
confidence: 99%
“…45 In P. gingivalisinfected bone marrow-derived macrophages, infection resulted in decreased mRNA transcription and protein expression of both PINK1 and Parkin, leading to an inhibition of mitophagy and a resultant accumulation of damaged mitochondria and reactive oxygen species (ROS). 44 Further research is needed to determine the mechanism by which P. gingivalis manipulates PINK1 and Parkin expression, and if this inhibitory effect on mitophagy can occur in dopaminergic neurons.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study analyzed the clinical specimens of gingival tissues from healthy and periodontitis patients and observed that the expression of PINK1, parkin and microtubuleassociated proteins light chain 3 (LC3) was significantly downregulated. 51 However, the PINK1 expression of hGFs exposed to different doses was found to be up-regulated or down-regulated. 52 It has been reported that PINK1-mediated mitophagy affects the development of disease through mitochondria-dependent apoptosis pathway 53 or inflammation regulation, 54 and it also exists in the pathogenesis of periodontitis.…”
Section: Pten-induced Putative Kinase 1 (Pink1) Is An Autophagy-relatedmentioning
confidence: 96%
“…It resides in the outer mitochondrial membrane (OMM) of the mitochondria, initially lacking in expression, but would accumulate in the OMM during mitochondrial damage, transferring parkin from the cytoplasm to the OMM and triggering mitophagy. A recent study analyzed the clinical specimens of gingival tissues from healthy and periodontitis patients and observed that the expression of PINK1, parkin and microtubule‐associated proteins light chain 3 (LC3) was significantly down‐regulated 51 . However, the PINK1 expression of hGFs exposed to different doses was found to be up‐regulated or down‐regulated 52 .…”
Section: Mitophagy and Periodontitismentioning
confidence: 99%
See 1 more Smart Citation